Enhancement of low velocity impact properties of bamboo/glass fibre hybrid composites using carbon nanotubes for aerospace structural applications - Mohd Nor, Ariff Farhan (2018)
Recently, polymer nanocomposites have been fabricated using carbon nanotubes (CNTs) as reinforcement nanofillers. However, the effect of incorporating CNT into hybrid polymer composites with natural fibre is not clear. This study investigated the effect of using multi-walled carbon nanotube material (MWCNT) as the nanofiller in bamboo/glass hybrid composites on the mechanical properties (tensile and flexural) and impact properties. Composites containing various weight fractions of CNTs (0.1 wt.%, 0.3 wt.%, 0.5 wt.%, and 1.0 wt.%) were produced thus compared with the control hybrid composites in tensile and flexural properties. Meanwhile, only 0.5 wt.% CNT was compared with the control hybrid composites in low velocity impact (LVI) test at various energy levels from 7J to 35J and then subjected to the compression after impact (CAI) test for further analysis. The hybrid composites were prepared with epoxy resin by hand lay-up method. The experimental results revealed an increase in the tensile strength of the composites with the addition of up to 0.5 wt.% CNTs (+7.73% over the control hybrid). However, beyond this value, i.e., with 1.0 wt.% CNT additives, the composite strength showed a remarkable decrease (-36.8% compared with the control hybrid). The decrement supported with Field Emission Scanning Electron Microscopy (FESEM). Moreover, introducing CNTs into hybrid composites resulted reduced the flexural properties with increasing weight fractions as low as 8.45% compared with the controls. Besides that, LVI showed the enhancement of CNTs in hybrid composites contributed towards the improvement in impact resistance (9.21% less in energy absorbed and maximum of +36.2% in term of peak force compared to the control hybrid) and CAI strength up to 23.7% corresponding to the controls. In sum, the tensile properties increased with the addition of up to 0.5 wt.% CNTs and increased the impact properties including CAI properties when introducing CNTs into the hybrid composites, but there was a decrease in the flexural properties. Hence, this thesis gives better understanding on the newly-hybridisation material’s mechanical properties.